EVALUASI KINERJA GURU RUMPUN PAI DI MADRASAH IBTIDAIYAH NEGERI 2 TANJUNG BERINGIN KABUPATEN KAUR - Intan Utami (UIN Fatmawati Sukarno Bengkulu, 2018)
This study aims to determine the performance evaluation PAI clumps in the planning, implementation and evalua- tion of learning in the State Islamic Elementary School (MIN) Tanjung Beringin District Kaur. These types of research, including research evaluation, data collection method in this research is to use the techniques of observation, interviews, questionnaires and documentation. The conclusion of this paper that the teacher performance MIN 2 Tanjung Beringin clumps of PAI in the planning of the learning process quite well. Planning is used in learning is always made at the beginning of the semester. How- ever, there are weaknesses in the preparation of the plan, namely the lack of planning time is written in the plan, structuring the learning background, development of instructional media and learning resources are not well planned. 2 MIN teacher perfor- mance Tanjung Beringin clump PAI has been good and in accordance with the regulations, both in the open class, delivering course material, using teaching methods, using instructional media, classroom management and lesson closes. 2 MIN teacher performance Tanjung Beringin clump PAI is good enough to evaluate conformity with the provisions. Planned evaluation conducted by the teacher MIN 2 Tanjung Beringin already accommodated in the lesson plan, so already scheduled. But for the evaluation that is impromptu, its implementation depends on the purpose of the material being taught